Study on Modification and Tooth Tip Sharping Analysis of Orthogonal Arc Tooth Face Gears - Zhanrong Feng; Guangjin Xiong; Lingfeng Gao; Chao Luo (Jixie chuandong, 2022)
Cylindrical gears with arc teeth as imaginary knife， which generate orthogonal arc tooth face gears using the envelope forming theory. Tooth surface equations of cylindrical gears with arc teeth and face gears are derived， which are based on differential geometry calculation and principle of gear meshing. Mathematical models of working tooth surface and transitional tooth surface are established based on Matlab. With the radius of tooth surface of cylindrical gears with arc teeth changed， the changes of tooth thickness， tooth width and contact line of face gears and the influence on contact trace are compared and analyzed by modifying of the face gear. Finally, through deriving the tooth point set of the face gear before and after modification， the entity modeling in the CATIA parts design is carried out. It is concluded that， with the increase of the radius of concave tooth surface of cylindrical gears with arc tooth， the outer radius of the face gear will have an augment. In the meanwhile， the phenomenon of tooth tip sharpening of face gear will change， that is the tooth thickness at the outer radius of the face gear increases gradually， the contact line has little change. The conclusions have laid a foundation for future research on partial load characteristics of face gears.